10x+2=4(2x-3)

Simple and best practice solution for 10x+2=4(2x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x+2=4(2x-3) equation:


Simplifying
10x + 2 = 4(2x + -3)

Reorder the terms:
2 + 10x = 4(2x + -3)

Reorder the terms:
2 + 10x = 4(-3 + 2x)
2 + 10x = (-3 * 4 + 2x * 4)
2 + 10x = (-12 + 8x)

Solving
2 + 10x = -12 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
2 + 10x + -8x = -12 + 8x + -8x

Combine like terms: 10x + -8x = 2x
2 + 2x = -12 + 8x + -8x

Combine like terms: 8x + -8x = 0
2 + 2x = -12 + 0
2 + 2x = -12

Add '-2' to each side of the equation.
2 + -2 + 2x = -12 + -2

Combine like terms: 2 + -2 = 0
0 + 2x = -12 + -2
2x = -12 + -2

Combine like terms: -12 + -2 = -14
2x = -14

Divide each side by '2'.
x = -7

Simplifying
x = -7

See similar equations:

| 8m-2=-3 | | 2.5(10x+8)+3x= | | 10x-2=4(2x-3) | | 2n*n-5=3n*n^2*n*4 | | 4x^3+5x^2-18x+9=0 | | 3.5x+215=495 | | 30/y=6/1/5 | | 2(3x-7)-10=20 | | -4x-118=116+9x | | 21+x=-39 | | 2[7-5(1-x)]+6x=-12+3[6(x+1)-3x] | | -3.7t-4.1=6.3t+6 | | 21+x=-31 | | 3x+100=4x+x | | X+3=y-5 | | (x+7)+(2x-1)+(2x+3)=79 | | 3n+n+5=37 | | (12y+9x)-(x-y)= | | -3(5s-6)-18=-3(7s+2)-3 | | 3/4x2=21 | | 5X/6-3/8=7X/4 | | 16x-1024/x2 | | 4(n-25)=9n | | 18000+36000r+18000r^2=0 | | 100-207/8 | | 24.6176=3.14r^2 | | 4x-12=7+7x-4 | | 0.8=5.8/x | | 1.2x+5=3.4 | | 2x^3+3x^2-29x-60=0 | | (2/3)/(3/11) | | 18000+36000r+18000r^2=0 |

Equations solver categories